Antiproliferative Effect of Bioaccessible Fractions of Four Brassicaceae Microgreens on Human Colon Cancer Cells Linked to Their Phytochemical Composition - Beatriz de la Fuente; Gabriel López-García; Vicent Máñez; Amparo Alegría; Reyes Barberá; Antonio Cilla (MDPI AG, 2020)
The antiproliferative effect of the bioaccessible fractions (BFs) of four hydroponic Brassicaceae microgreens (broccoli, kale, mustard and radish) was evaluated on colon cancer Caco-2 cells vs. normal colon CCD18-Co cells after 24 h treatment with BFs diluted 1:10 v/v in cell culture medium. Their bioactivity was compared with the digestion blank, while the colon cancer chemotherapeutic drug 5-fluorouracil was used as a positive control. Cell viability (mitochondrial enzyme activity assay (MTT test) and Trypan blue test) and mechanisms related to antiproliferative activity (cell cycle, apoptosis/necrosis, mitochondrial membrane potential, reactive oxygen species (ROS) production, Ca2+ and glutathione (GSH) intracellular content) were studied. All microgreen BFs increased ROS and decreased GSH, altering the redox status and causing mitochondrial membrane dissipation followed by a general cell cycle arrest in G2/M and apoptotic cell death via a Ca2+-independent mechanism. As a result, the antioxidant bioactive compounds present in these microgreen species reduced the proliferation of tumoral cells (10 to 12.8% -MTT or 20 to 41.9% -Trypan blue), showing lesser effects with broccoli microgreens, in line with their lower ascorbic acid content and total antioxidant capacity. Therefore, the daily intake of microgreens within a balanced diet could be a preventive nutritional strategy to reduce the burden of chronic degenerative diseases such as colon cancer.